2014
DOI: 10.7287/peerj.preprints.186v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence of twin embryos in the eastern bluebird

Abstract: We report the first record of presumed twinning in eastern bluebird (Sialia sialis) and provide a review of all previously reported twinning events in wild birds. A nest containing twin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Evolution MegaLab, a European study, successfully gathered a modern sample of an indicator species with a genetically based trait (color) that could be evolutionarily responsive to external pressures (climate, changing predation) and showed that variations in color in the target snail species were likely not the result of changing climate but were caused by changing predation pressures (41). Long-term monitoring projects like these also facilitate rare detections in which many eyes are needed, but only a few will actually find something [see, for example, publications from the Lost Ladybug Project indicating the detection of new ladybug species (42), from NestWatch on a first official record of twinning in bluebirds (43), and from routine cetacean surveys in Israel documenting the first ever recorded instance of a gray whale there (44)]. Together, these projects cover a spectrum of scientific approaches, ranging from post hoc or real-time pattern detection (Plant Watch, eBird, Voyages Bio Sous-Marine) to experimental or observational hypothesis testing (Monarch Health, Evolution MegaLab, Belly Button Biodiversity), illustrating the scientific, geographic, and temporal potential of citizen science.…”
Section: Ecological Research Outcomes Of Note From 2009 Through 2013mentioning
confidence: 99%
“…Evolution MegaLab, a European study, successfully gathered a modern sample of an indicator species with a genetically based trait (color) that could be evolutionarily responsive to external pressures (climate, changing predation) and showed that variations in color in the target snail species were likely not the result of changing climate but were caused by changing predation pressures (41). Long-term monitoring projects like these also facilitate rare detections in which many eyes are needed, but only a few will actually find something [see, for example, publications from the Lost Ladybug Project indicating the detection of new ladybug species (42), from NestWatch on a first official record of twinning in bluebirds (43), and from routine cetacean surveys in Israel documenting the first ever recorded instance of a gray whale there (44)]. Together, these projects cover a spectrum of scientific approaches, ranging from post hoc or real-time pattern detection (Plant Watch, eBird, Voyages Bio Sous-Marine) to experimental or observational hypothesis testing (Monarch Health, Evolution MegaLab, Belly Button Biodiversity), illustrating the scientific, geographic, and temporal potential of citizen science.…”
Section: Ecological Research Outcomes Of Note From 2009 Through 2013mentioning
confidence: 99%
“…However, the GSE supplementation reduced the incidence of double-yolk eggs. The double-yolked avian egg is a common physiological process in commercial species of poultry (40,41). Double-yolk eggs are formed when two F1 follicles ovulated within three hours of each other become enclosed in one egg (42), and estimated to occur in 4 ~…”
Section: Gse Reduced Ros Level In Egg Yolkmentioning
confidence: 99%
“…12.5% of broiler breeder pullet eggs in the first 3 months of laying (43,44). Double-yolk eggs are considered as a loss to overall commercial hatcheries because of their relatively lower yolk fertility rate due to their smaller yolk size and markedly lower hatchability rate (40,45). Thus, maternal…”
Section: Gse Reduced Ros Level In Egg Yolkmentioning
confidence: 99%
“…33-34 days of incubation, likewise the twin emu embryos described by Wierci nska and Szczerbi nska (2005). Particularly interesting seems to be the case of two genetically identical emu chicks (Bassett et al 1999) and the case of successful hatching of eastern bluebird (Sialia siali) twins (Bailey and Clark 2014). The latter is even more interesting considering that the chicks hatched as a result of natural incubation without human interference.…”
Section: Introductionmentioning
confidence: 99%